Parents' information and support needs when their child is diagnosed with type 1 diabetes: a qualitative study. (29th July 2014) - Rankin, David; Harden, Jeni; Waugh, Norman; Noyes, Kathryn; Barnard, Katharine D.; Lawton, Julia
Abstract: Aim and objective: The aim of this study was to describe and explore parents' information and support needs when their child is diagnosed with type 1 diabetes, including their views about the timing and chronology of current support provision. Our objective was to identify ways in which parents could be better supported in the future. Design and participants: Semi‐structured interviews were conducted with 54 parents of children with type 1 diabetes in four paediatric diabetes clinics in Scotland. Data were analysed using an inductive, thematic approach. Findings: Parents described needing more reassurance after their child was diagnosed before being given complex information about diabetes management, so they would be better placed psychologically and emotionally to absorb this information. Parents also highlighted a need for more emotional and practical support from health professionals when they first began to implement diabetes regimens at home, tailored to their personal and domestic circumstances. However, some felt unable to ask for help or believed that health professionals were unable to offer empathetic support. Whilst some parents highlighted a need for support delivered by peer parents, others who had received peer support conveyed ambivalent views about the input and advice they had received. Conclusions: Our findings suggest that professionals should consider the timing and chronology of support provision to ensure that parents' emotional and informational needs are addressed when their child is diagnosed and that practical advice and further emotional support are provided thereafter, which takes account of their day‐to‐day experiences of caring for their child.